Functional Food Plants and their Potential Antiviral and Immunomodulatory Properties: the Covid-19 Perspective : Food as a potential weapon against Covid-19 - Din, Misbahud; Zia, Fatima; Khalil, Ali Talha; Ali, Muhammad; Shinwari, Zabta Khan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The pandemic of coronavirus disease (Covid-19) which is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is continuously hitting the world and millions of individuals have been affected so far. Limited therapeutic options are available for the treatment of Covid-19 while scientists around the globe are working hard to make the vaccines clinically available to the maximum human population. Alarmingly, SARS-CoV-2 variants of SRAS-CoV-2 are emerging in different regions of the world, hence threatening the efficacy of the clinically available vaccines. In such a scenario, the utilization of medicinal plants or traditional medicine could be the most preferred choice along with the precautionary measure to be adopted against the Covid-19. The current article has summarized few important food plants that have previously exhibited promising immunomodulatory or antiviral activities. These medicinal plants could be suggested for boosting the immune system and could be utilized against their utilization against SARS-CoV-2. It could be concluded that medicinal plants especially Allium sativum, Curcuma longa, and Allium cepa along with other plants/herbs/spices could not only be used against SARS-CoV-2 but also other viral, bacterial, or other parasitic diseases other prevalent diseases prevalent in the region.